RFID self-service innovation of reader service in University Library. Take Baise University as an example - Hu, Liyun (Technium Social Sciences Journal, 2021)
Taking Baise University as an example, this paper introduces in detail the University Library in order to better serve readers, keep pace with the times, implement innovative service mode, and apply RFID self-service for innovative service. RFID is a kind of wireless communication technology, which can identify specific targets and read and write relevant data through radio signals without establishing mechanical or optical contact between the identification system and specific targets. It is also called RFID self-service machine that readers use RFID machine to borrow and return books by themselves at the screen terminal of RFID reader. The self-service of university library not only facilitates readers, but also saves time, improves the level of management technology and work efficiency, and promotes the development of university library work.